Α11β1 integrin‐mediated MMP‐13‐dependent collagen lattice contraction by fibroblasts: Evidence for integrin‐coordinated collagen proteolysis. Issue 5 (28th January 2013) - Barczyk, Malgorzata M.; Lu, Ning; Popova, Svetlana N.; Bolstad, Anne Isine; Gullberg, Donald
Abstract: We have previously determined that integrin α11β1 is required on mouse periodontal ligament (PDL) fibroblasts to generate the force needed for incisor eruption. As part of the phenotype of α11 −/− mice, the incisor PDL (iPDL) is thickened, due to disturbed matrix remodeling. To determine the molecular mechanism behind the disturbed matrix dynamics in the PDL we crossed α11 −/− mice with the Immortomouse and isolated immortalized iPDL cells. Microarray analysis of iPDL cells cultured inside a 3D collagen gel demonstrated downregulated expression of a number of genes in α11‐deficient iPDL cells, including matrix metalloproteinase‐13 (MMP‐13) and cathepsin K. α11 −/− iPDL cells in vitro displayed disturbed interactions with collagen I during contraction of attached and floating collagen lattices and furthermore displayed reduced MMP‐13 protein expression levels. The MMP‐13 specific inhibitor WAY 170523 and the Cathepsin K Inhibitor II both blocked part of the α11 integrin‐mediated collagen remodeling. In summary, our data demonstrate that in iPDL fibroblasts the mechanical strain generated by α11β1 integrin regulates molecules involved in collagen matrix dynamics. The positive regulation of α11β1‐dependent matrix remodeling, involving MMP‐13 and cathepsin K, might also occur in other types of fibroblasts and be an important regulatory mechanism for coordinated extracellular and intracellular collagen turnover in tissue homeostasis. J. Cell. Physiol. © 2012 Wiley Periodicals, Inc.